PERKEMBANGAN FISIK KOTA DUMAI SETELAH PEMEKARAN - , WILSUBANDI; , Ir. Gunung Radjiman, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In her early stage, Dumai city was only a small village on the east coast of Riau Province. In 1999 Dumai City become an autonom cities, and such status triggered city development. This study aimed to describe the groeth pattern of the City Dumai before and after the new status development. This is a deductive type of research, using qualitative with spatial analysis. The research was conducted through a series of studies logical (rational) the parameters against, variables and indicators derived from the theoretical basis. The study found that the physical pattern of the city before the expansion from Bengkalis was a concentric pattern. After the expansion in the year 1999- 2004, the pattern become linear patterns. In the year 2004-2009, the pattern change into leap frog pattern. The most dominant factor affecting the physical development of the city is economic factor. The study recommends the important of a more depth studies about the potentials and constraints of Dumai city for future development as well as consistent the application of spatial city planning so that the development of Dumai city would be more balanced and equally in all directions.